Ambipolar materials and devices - Zhou, Ye; Han, Su-Ting (Smart materials, 2021)
Ambipolar materials represent a class of materials where positive and negative charge carriers can both transport concurrently. In recent years, a diverse range of materials have been synthesized and utilized for implementing ambipolar charge transport, with applications in highdensity data storage, field effect transistors, nanotransitors, photonic memory, biomaterial-based memories and artificial synapses. This book highlights recent development of ambipolar materials involving materials design, fundamental principles, interface modifications, device structures, ambipolar characteristics and promising applications. Challenges and prospects for investigating ambipolar materials in electronics and optoelectronics are also discussed. With contributions from global leaders in the field, this title will appeal to graduate students and researchers who want to understand the design, materials characteristics, device operation principles, specialized device application and mechanisms of the latest ambipolar materials.